Os caminhos do Caminho das Graças: religiosidade, paisagem e identidade - Augustin, Roberta Lopes (Universidade do Vale do Rio dos Sinos, 2014)
The present paper is a study about the overlapping of religiosity, landscape(Scenery) and identity, through an ethnographic fieldwork as the “Caminho das Graças” (Path of Grace), a development of religious tourism that focuses on providing a space for local faith. Conceived and maintained by the local residents of Banhado Grande, which is located between two tourist attractions – “Parque do Caracol” and “Parque da Ferradura”. It is in a rural municipality of Canela, Rio Grande do Sul, Brazil. The Path is seven kilometers across small farms and local families homes. In front of each property prepared from these families, a capital with Saints of devotion, such conduct which has reference from the Catholic Saints devotional imaging. The materials used in the construction of the capitals as well as their aesthetic conceptions are varied and creative, explaining the ways of use or adjust the local resources. This articulation produces a religious hybrid setting path, drawn from the convergence of place and no place, composed from tourist assemblages, religious, landscape and identity. The investigative process was accomplished by procedures guided by the ethnographic method, through situational analysis, based on participant observation, semistructured interviews, log books and audiovisual resources. Thus, the plurality of narratives was the scope for the analysis of the overlapping of local identity process through the identity of the action, as well as the contemporary religious interactions and their assemblages. This sociological analysis is based on phenomenological considerations that enable the design of intersubjectivity as a guideline for the understanding of the different spaces that the “Caminho das Graças” offers. The “Caminho das Graças” was observed as empirical context therefore intersubjective, plural and significant, which shows up as a subjective and complex biography. A scenario that establishes interactions through sociações (SIMMEL, 1996), from objetificadores processes (CSORDAS, 2008), elaborating out relational and setting the stories of the different places of the place enabling the investigation of the "soul of place" (YÁZIGI, 2002). Thus unfolds as a collective project that aims to provide welfare through spiritual experiences, from religiosity in touch with nature, experienced in the landscape the required reflexivity.
Keywords: Religiosidade; Identidade; Paisagem; Ação; Agenciamentos; Imbricações; Religiosity; Identity; Landscape; Action; Assemblages; Overlapping; ACCNPQ::Ciências Humanas::Sociologia